Two New Species of the Genus Calanopia (Copepoda, Calanoida, Pontellidae) from the Northern Levantine Basin (Mediterranean Sea) - Uysal, Z.; Shmeleva, A. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2004)
Представлено иллюстрированное описание двух новых видов рода Calanopia — Calanopia levantina Uysal et Shmeleva, sp. n. и Calanopia metu Uysal et Shmeleva, sp. n., найденных в зоопланктонных пробах, взятых сетью Нансена в слое 0–100 м в прибрежных водах моря Леванта. С. levantina близка к С. minor A. Scott и С. aurivillii Cleve, но отличается от них строением и вооружением пятой пары плавательных ног, строением (структурой) рострума и др. С. metu отличается от других видов этого рода грубой, ребристой широкояйцевидной формой тела с короткими торакальными шипами и короткой как бы спрессованной уросомой. Two new species, Calanopia levantina Uysal et Shmeleva, sp. n. and Calanopia metu Uysal et Shmeleva, sp. n. are described and figured. These species were found in the zooplankton collected by the Nansen net at 0–100 m depth along Turkish coastal waters in the northern Levantine Basin. C. levantina is closely related to C. minor A. Scott and C. aurivillii Cleve but differs from other species of this genus mainly by the structure and armature of the fifth leg, the structure of rostrum, etc. C. metu differs from other species of this genus by the robust form, body-wide-ovoid cephalosome with short thoracic spines and a short compressed urosome.